1992
DOI: 10.1001/archderm.1992.01680130066007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Panel Assessment of Photodamaged Skin Treated With Isotretinoin Using Photographs

Abstract: The clinical panel detected significantly better improvement in photodamaged-skin treated with isotretinoin than in such skin treated with vehicle. The panel provided an independent assessment of the effects of treatment uninfluenced by physical findings during treatment or information provided by the patients treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…It was confirmed that the application of 0.05% isotretinoin in combination with sunscreens improved the appearance of the fine wrinkles associated with photoaged skin [ 66 ]. The results were consistent with previously performed studies by other authors [ 64 , 65 ]. It can be concluded that most of the performed studies about topical application of isotretinoin for photodamaged skin showed statistically significant improvement in the overall appearance of the skin including fine lines and pigmentation.…”
Section: Clinical Evidencesupporting
confidence: 94%
“…It was confirmed that the application of 0.05% isotretinoin in combination with sunscreens improved the appearance of the fine wrinkles associated with photoaged skin [ 66 ]. The results were consistent with previously performed studies by other authors [ 64 , 65 ]. It can be concluded that most of the performed studies about topical application of isotretinoin for photodamaged skin showed statistically significant improvement in the overall appearance of the skin including fine lines and pigmentation.…”
Section: Clinical Evidencesupporting
confidence: 94%
“…Isotretinoin appears to be less irritating and perhaps less effective than tretinoin but this may be because it requires isomerization to tretinoin for activity. Two other studies 28,29 have reported improvement in fine wrinkles after 36 weeks of treatment comprising an initial 12‐week course of isotretinoin 0.05% cream followed by 24 weeks of a 0.1% formulation. The effectiveness of retinaldehyde (retinal) 0.05% cream for treatment of photoageing has been compared directly with 0.05% tretinoin and vehicle creams over an 18‐week period 30 .…”
Section: Topical Retinoids In the Management Of Photoageingmentioning
confidence: 97%
“…Armstrong et al ., 54 in a well‐conducted trial, reported significantly better improvement of photodamaged skin treated with 0.5–1.0% isotretinoin cream. Later, Sendagorta et al 55 .…”
Section: Photodamaged Skinmentioning
confidence: 98%